2022
DOI: 10.1037/xge0001196
|View full text |Cite
|
Sign up to set email alerts
|

“Do not teach them how to fish”: The effect of zero-sum beliefs on help giving.

Abstract: How do zero-sum beliefs—the beliefs that one person’s success is inevitably balanced by others’ failure —affect people’s willingness to help their peers and colleagues? In nine studies (and 2 supplementary studies, N = 2,324), we find consistent evidence for the relationship between the belief that success is zero-sum and help giving preferences. Across various hypothetical scenarios and actual help giving decisions, and even when the effort required for helping was minimal, zero-sum beliefs negatively predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Previous research has linked the zero‐sum mindset with social vigilance (Liu et al, 2019). Furthermore, studies have shown that the zero‐sum mindset can reduce employees' helping behavior in the organizational context (Chernyak‐Hai & Davidai, 2022; Sirola & Pitesa, 2017). Although our research focused on general charitable behavior rather than employees' helping behavior, it is important to consider the possibility that the zero‐sum mindset may provide an alternative explanation for our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has linked the zero‐sum mindset with social vigilance (Liu et al, 2019). Furthermore, studies have shown that the zero‐sum mindset can reduce employees' helping behavior in the organizational context (Chernyak‐Hai & Davidai, 2022; Sirola & Pitesa, 2017). Although our research focused on general charitable behavior rather than employees' helping behavior, it is important to consider the possibility that the zero‐sum mindset may provide an alternative explanation for our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, regardless of whether people are right or wrong to view politics as zero-sum, the implications of holding such beliefs may be substantial. Just as viewing status as zero-sum inhibits help-giving and motivates aggression irrespective of its veracity 51,73,85,86 , people who view politics as zero-sum may shield themselves from opposing views irrespective of the correctness of their beliefs.…”
Section: Limitationsmentioning
confidence: 99%
“…In contrast, viewing issues such as racial relations as non– zero-sum (i.e., that minorities do not benefit at the majority’s expense) increases support for policies that address racial inequality (Stefaniak et al, 2020). In general, the more people view a situation as zero-sum, the more they try to stifle others’ progress and the less they wish to offer help or support (Chernyak-Hai & Davidai, 2022; Esses et al, 2001; McGhee, 2021; Wilkins et al, 2015).…”
Section: Zero-sum Beliefs About Social Hierarchiesmentioning
confidence: 99%